PENGARUH MODEL PEMBELAJARAN SAVI BERBANTUAN PUZZLE GAMES TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS V SDN 26 SINGKAWANG - Ersa Safitri; Evinna Cinda Hendriana; Lili Yanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the differences, influences, and effectiveness of the use of the SAVI learning model assisted by puzzle games on the poetry writing skills of grade V elementary school students. The research uses a quantitative approach with a Pre-Experimental design in the form of One Group Pretest-Posttest Design. The population as well as the research sample is all grade V students of SDN 26 Singkawang which totals 29 students with saturated sampling techniques. Data collection was carried out through a poetry writing skills test. Data analysis used normality test, paired sample t-test, effect size test, and N-gain test. The results showed that there was a significant difference between poetry writing skills before and after treatment, with the value of t-count.=11.419 greater than ,t-table.=2.048. The influence of using the SAVI model assisted by puzzle games is relatively high with an effect size value of 2,378. In addition, the results of the N-gain test showed an increase of 63% in the category of quite effective. Thus, the SAVI learning model assisted by puzzle games can significantly improve students' poetry writing skills and is suitable for use in learning Indonesian in elementary schools.